An Archeological Survey of the Gila River Farms Expansion, Pinal County, Arizona - Effland, Jr., Richard W. (Archaeological Consulting Services, Ltd.); Sullivan, Mary (Archaeological Consulting Services, Ltd.); Sawyer-Lang, Monique (Archaeological Consulting Services, Ltd.); Green, Margerie (Archaeological Consulting Services, Ltd.) (the Digital Archaeological Record)
An archaeological clearance survey of the proposed Gila River Farms Expansion area was undertaken by Archaeological Consulting Services, Ltd. (ACS). This survey was performed in accordance with the provisions and regulations of the National Historic Preservation Act in order to locate, identify, and assess cultural resources that might be adversely impacted when the Gila River Indian Community (GRIC) begins to utilize this land for agriculture. A total of four sites, four artifact scatters, and 79 isolated finds were recorded during the survey. This report describes these cultural resources and assesses the potential effects resulting from their loss if development of this land were to occur.